A case report on ovarian dermoid cyst - D., Rita; Devi, Aadireddy (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Ovarian dermoid cyst, also known as a mature cystic teratoma, is a benign embryonal tumor. Dermoid cysts account for approximately 10-25% of all ovarian tumors and comprise about 60% of all benign ovarian neoplasms. They are common in adolescent and young age and carry minimal risk of malignant transformation. A case of 14 year old adolescent girl presented to OBG outpatient department at Navodaya medical college, Raichur with compliant of abdominal pain since 1 month. Ultrasonography features suggestive of right dermoid cyst, further evaluated with tumour markers. Managed with laparotomy and proceed. Understanding the epidemiology, clinical features and imaging characteristics of dermoid cysts is essential for accurate diagnosis, to prevent complications and treatment planning.